Brain iron quantification by MRI in mitochondrial membrane protein‐associated neurodegeneration under iron‐chelating therapy. (2nd December 2014) - Löbel, Ulrike; Schweser, Ferdinand; Nickel, Miriam; Deistung, Andreas; Grosse, Regine; Hagel, Christian; Fiehler, Jens; Schulz, Angela; Hartig, Monika; Reichenbach, Jürgen R.; Kohlschütter, Alfried; Sedlacik, Jan
Abstract Therapeutic trials for Neurodegeneration with Brain Iron Accumulation have aimed at a reduction of cerebral iron content. A 13‐year‐old girl with mitochondrial membrane protein‐associated neurodegeneration treated with an iron‐chelating agent was monitored by R2 relaxometry, R2* relaxometry, and quantitative susceptibility mapping to estimate the brain iron content. The highly increased brain iron content slowly decreased in the substantia nigra but remained stable for globus pallidus. The estimated iron content was higher by R2* compared to R2 and quantitative susceptibility mapping, a finding not previously observed in the brain of healthy volunteers. A hypothesis explaining this discrepancy is offered.